Testing an Extended Reasoned Action Framework to Predict Intention to Purchase Fruits With Novel Shapes. Issue 2 (3rd April 2017) - Rodriguez, Lulu; Kulpavaropas, Supathida; Sar, Sela
ABSTRACT: This study explored the influence of consumers' attitudes, subjective norms, and novelty-seeking on their intention to purchase fruits of unconventional or novel shapes. Based on the results of an online survey of consumers from around the world, and guided by an extended version of the theory of reasoned action, the findings showed that consumers' intention to purchase buddha- and baby-shaped pears was determined largely by the attitudes they hold about fruits with uncharacteristic shapes, but not by subjective norms. Novelty-seeking was strongly correlated with purchase intention. Young consumers with lower incomes were more likely to buy the non-conventional-shaped products than older consumers with higher incomes.